2004
DOI: 10.1246/cl.2004.594
|View full text |Cite
|
Sign up to set email alerts
|

Useful Method for Direct Introduction of the Photoaffinity 3-(4-Hydroxyphenyl)-3-trifluoromethyldiazirine Group

Abstract: A convergent and efficient preparation method of the photoaffinity 3-(4-alkoxyphenyl)-3-trifluoromethyldiazirine derivatives was established by direct introduction of the photoaffinity group utilizing the Mitsunobu reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The etherification was also possible under Mitsunobu conditions. [24] However, the yield was lower and separation of the byproducts turned out to be problematic. The final oxidation of the aldehyde 21 to the acid 22 was rather problematic.…”
Section: Resultsmentioning
confidence: 99%
“…The etherification was also possible under Mitsunobu conditions. [24] However, the yield was lower and separation of the byproducts turned out to be problematic. The final oxidation of the aldehyde 21 to the acid 22 was rather problematic.…”
Section: Resultsmentioning
confidence: 99%
“…Pd(0)-catalyzed coupling of alkyne 10 with 3-bromo-2-propyn-1-ol gave 11 and subsequent hydrogenation with 10% Pd/C afforded 12. After the reaction of 12 with 3-(4-hydroxyphenyl)-3-trifluoromethyldiazirine, which was synthesized by the method of Lu et al, 12) under the Mitsunobu reaction conditions, 13) hydrolysis of the acetyl group and sequential deprotection of MOM ether afforded 13. The inhibition of complex I activity was determined by NADH oxidase assay using bovine heart submitochondrial particles.…”
Section: Resultsmentioning
confidence: 99%
“…The p-diazirinyl phenol 10 has been utilized to form ether linkage in the Mitsunobu reaction in previous reports. 18 The reported reaction was set at room temperature for all compounds with good yields. Our results indicated that Mitsunobu reaction of sucrose derivative 2 and diazirinyl phenols 9 or 10 were regulated by two factors.…”
mentioning
confidence: 99%